Cacing Parasit Saluran Pencernaan Pada Hewan Primata di Taman Satwa Kandi Kota Sawahlunto Provinsi Sumatera Barat - Fadhilah Rahmah; - Dahelmi; Siti Salmah (Jurnal Biologi Universitas Andalas, 2013)
A study about gastrointestinal helminths of four species of primate was conducted from June to September 2012 at Taman Satwa Kandi Sawahlunto and Laboratory of Animal Taxonomy, Andalas University, Padang. This study aimed to identify species of gastrointestinal helminths of the primates and to determine the prevalence of the parasites. This study used non-invassive method by collecting fresh fecal samples from ten individuals of captivated primates and collecting soil samples around exhibition cages. Those samples were examined by using floating-centrifuge and filtration methods. The result showed that in the primates fecal were found eggs of Ascaris lumbricoides (prevalence= 60%), eggs of Trichuris sp. (10%), rhabditiform larvae of Strongyloides stercoralis (20%) and rhabditiform larvae of Necator americanus (20%). In the contaminated soil were found eggs of Ascaris lumbricoides, eggs of Enterobius vermicularis (10%), eggs of Necator americanus and rhabditiform larvae of Strongyloides stercoralis. This result indicated those primates were vulnerable to the infection of helminth parasites.Keywords : gastrointestinal helmints, prevalence, primates, Taman Satwa Kandi